Temporal juxtapositions: Views of an alternate timeline of Gamla stan - Rahahleh, Osama (My University, 2021)
What would it be like to re-imagine lost structures from the architectural history of a place and project them into an alternate present? The premise of the thesis is to bring attention back onto lost forgotten architectural moments from history and re-imagine their attributes and potential once retrieved and re-imagined through computation tools. If these lost physical moments were to survive the concept of time; how would they appear in the present? And what would their qualities be? Can this approach be a way of form-finding? The thesis envisioned an alternate present where the past and the present meet in a time-defying context. The nature of architectural imaginations manifest in different forms and consequentially explore the potential lost structures can hold once seen through the lens of speculative design tools. In order to experiment with lost buried values -- both physical attributes and form of lost architectural structures, the lost original “Tre Kronor” castle was selected. The lost castle provided a canvas and testbed to deploy and test different methods and approaches to speculative design. The process seeks to explore both the original form and spatial con - figuration of the lost castle, in addition to re-imagining the different parts of the castle once introduced into the speculative context of an alternate Gamla stan. The thesis was an open investigation into speculative design aspects and how reflecting onto the past can serve as a plat - form to make more self-aware speculations into the present, and consecutively the future. A final outcome presents itself in the form of the Nya Gamla Stan - another reality presented in text and illustrations. Nya Gamla stan is where temporal juxtapositions introduce a sample of the results of the thesis research. In addition to a catalog of all digital models created in the process.
Keywords: juxtaposition, form-finding, temporal speculation, fiction, count - er-factual, alternate reality